SECURITY OF HOTSPOTS IN BUSES - Kozieł, Grzegorz; Maluga, Jakub (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
Paper discusses the security of the mobile hotspots mounted in buses. The analysis of vulnerabilities is done. Chosen aspects of security are examined. Finally the proposal of proper mobile hotspot protection is described.